(untitled) (International Journal of Food and Nutritional Sciences, 2024)
In contemporary data management systems, ensuring the security and integrity of stored documents is paramount. One prevalent approach leverages blockchain technology, integrating cryptography hashing algorithms such as SHA-256 for enhanced protection. When a document is uploaded, it undergoes hashing to generate a unique cryptography hash. This hash is then embedded into a block chain transaction, alongside relevant metadata, and added to the block chain. Once recorded, the transaction becomes immutable, safeguarding the document’s integrity. Verification involves retrieving the hash from the block chain and comparing it with the computed hash of the current document. This process ensures tamper-proof records and authenticates the document’s integrity. Utilizing blockchain in this manner establishes a decentralized, secure environment, mitigating risks associated with centralized storage solutions.